From Blackboard to Digital Screen (Transformation of Islamic Religious Education in Plus Classes at Zainul Hasan 1 Genggong Middle School) - Dewi Shinta Kurnia Ilahi (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
This research examines the transformation of Islamic Religious Education (PAI) learning in the Plus Class of Zainul Hasan 1 Genggong Middle School, which previously used traditional methods with blackboards, now switching to the use of digital technology. The background to this research was triggered by the development of information technology which is changing the education system and the need to update learning methods to make them more relevant to the digital era. With a descriptive qualitative approach, this research explores the transition process, the challenges faced by teachers and students, and the impact of the use of technology on the quality of learning. The research results show that the application of digital technology enriches the learning experience, increases student engagement, and provides more flexible access to material. However, the main challenges faced are the need for training for teachers and limited infrastructure improvements, which need to be addressed immediately to optimize the potential for digital transformation in PAI education.